Criminal Law Perspectives on Medical Legal Issues in Telemedicine - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Antai, Godswill Owoche; Onwubiko, Kelechi (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2025)
Digital technology has transformed healthcare globally, with telemedicine playing a pivotal role in expanding access to medical services in remote and underserved areas. In Nigeria, however, the practice of telemedicine raises complex medico-legal issues that directly intersect with criminal law. This study examines criminal law perspectives on telemedicine in Nigeria, with particular emphasis on medical liability, patient confidentiality, data protection, and accountability for malpractice or negligence. The research employed a quantitative approach, administering 303 questionnaires to respondents across Nigeria and analyzing the data to assess perceptions of telemedicine and its legal implications. The findings indicate, first, that telemedicine holds significant potential to strengthen Nigeria’s healthcare system, but its effectiveness is constrained by serious challenges, including the absence of a comprehensive regulatory framework, inadequate protection of patient data, and uncertainty regarding criminal liability for medical errors and breaches of confidentiality. Second, the study underscores the urgent need for Nigeria to establish robust laws, ethical guidelines, and medical regulations that specifically address issues of criminal liability, professional responsibility, and patient protection in telemedicine. The adoption of such frameworks would provide legal certainty, enhance accountability, and foster greater public trust in digital healthcare delivery.